Regularity of hardening conditions of a 100t steel ingot in a thin-wall mold - G. A. Anisovich; I. A. Samojlovich; V. I. Timoshpolsky; I. A. Trusova; O. G. Khopova (Литьë и металлургия)
Оп the basis of mathematical modeling of a large ingot hardening process in the mold the regularity of formation of the temperature field in the ingot and in the mold are investigated when thin-wall molds are used.